Identificação e rastreabilidade de Cannabis sativa por meio de sistema multiplex de microssatélite (STR) - Ribeiro, Lucas de Oliveira Pereira (2019)
The consumption of psychoactive substances that may cause harm to the individual is a medical and social concern since 1925. Nowadays, marijuana still is the most consumed drug worldwide. Despite the decrease of illegal consumption in European countries, in the America continent it is growing. In Brazil, according to reports, approximately 225 thousand kilograms were apprehended by the Brazilian Federal Police. As an illicit drug in most of the countries, marijuana acquisition by consumers occurs through the illicit market. It is estimated that, worldwide, 65 per cent of the organized crime is involved with narcotraffic. One third of Brazilian prison population respond for crimes associated with drugs markets, in Rio Grande do Sul (RS) this number is about one quarter. The marijuana seized in RS come from three main sources: Paraguay, Uruguay, and Marijuana Polygon (region alongside São Francisco river that extends between the states of Bahia and Pernambuco). Besides these known paths, a new incoming source can be observed through postal office seeds apprehension in the past few years. The analysis of two 13-loci STR multiplex panels (proposed by Houston and collaborators, 2015 and 2017), 94 samples of Cannabis sativa trafficked in Brazil were investigated. Both systems were effective in individualizing and origin differentiating each sample. The random match probability of two unrelated samples for Panel 2015 and Panel 2017 were one in 65 billion and one in 430 million, respectively. In addition, Panel 2015 correctly classified 99% of all samples according to its region, while Panel 2017 classified 96%. The Principal Coordinate Analysis (PCoA) of Panel 2015 clearly distinguish the groups of seizure according to their regions. Overall, the comparison of the forensic results obtained for both panels allowed to observe a significant efficiency improvement in individualization and origin identification of Brazilian samples when using Panel 2015. Utilizing the genotype of all 19 markers, it was possible to identify a genetic variance among the groups concordant with the geographical region of each seizure. In comparison, the analysis of all STR markers collectively showed better results than those obtained with Panel 2015. This gain in informative power was expected, since 7 STRs were added. Although, the effort and cost of analyzing two 13-loci STR systems in order to obtain all 19 loci should be considered and might not be advantageable. In conclusion, Panel 2015 proposed by Houston et al. (2015) demonstrated better results when compared with Panel 2017, being a reliable tool for the Brazilian Police intelligence.